The Non-Cash Food Assistance Program (BPNT) Policy is being Implemented in Gegesik Wetan through E-warung - Riyani, Ade; Rianto, Agus (ann4publisher@gmail.com, 2023)
In Indonesia as well as other parts of the world, poverty has become a problem. The Non-Cash Food Assistance Program (BPNT) is one of the government's initiatives to combat poverty. The government provides non-cash food aid (BPNT) to address the community's essential requirements. The monthly aid amount of Rp 200,000/KPM can only be applied to grocery purchases at e-warung partnered with banks. It is transferred through an electronic account once per month. This study aims to evaluate how the hamlet of Gegesik Wetan will administer the non-cash food assistance program (BPNT) via e-warung. A descriptive method with a qualitative approach was employed in this investigation. Techniques for gathering data include interviewing and documenting. This study's subject is the use of Non-Cash Food Assistance (BPNT) via e-warung in the village of Gegesik Wetan. This study applies George Edward III's theory to four indicators: bureaucratic organization, communication, resources, and disposition. The findings indicated they could have been at their best when the four markers were met. Several challenges must be overcome for the program to continue in the future.